Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12905-021-01494-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of educational intervention on improvement of physical activities of middle-aged women

Abstract: Background Regular physical activity has important health benefits for women. The present study aimed to investigate the effect of theory-based educational interventions on the improvement of physical activities of middle-aged women. Methods This experimental study was conducted on 160 middle-aged women referred to Ahwaz health centers Iran in 2017 who were selected through the cluster sampling method. They were randomly divided into two groups: in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Additionally, adhering to regular exercise aids these individuals in alleviating stress and anxiety (24). Numerous studies have demonstrated the effectiveness of educating women on physical activity as a means of increasing their own levels of engagement (25)(26)(27)(28)(29)(30). Nevertheless, it is imperative to identify the various factors that influence women's participation in physical activities due to their complex intersection with financial circumstances, employment status, environmental conditions, family dynamics, cultural norms and sub-culture values, systems, religious practices, educational background, and socio-demographic traits (17,26,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
mentioning
confidence: 99%
“…Additionally, adhering to regular exercise aids these individuals in alleviating stress and anxiety (24). Numerous studies have demonstrated the effectiveness of educating women on physical activity as a means of increasing their own levels of engagement (25)(26)(27)(28)(29)(30). Nevertheless, it is imperative to identify the various factors that influence women's participation in physical activities due to their complex intersection with financial circumstances, employment status, environmental conditions, family dynamics, cultural norms and sub-culture values, systems, religious practices, educational background, and socio-demographic traits (17,26,(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43).…”
mentioning
confidence: 99%